(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article reviews issues that examine the concept known as “Alpha engendering,” whose main characteristic is the valorization of technological autonomy in the contemporary educational context. The approach is based on dynamic pedagogical practices that reconcile the valorization of the collective with respect for individuality, promoting an agile and innovative formative process with the potential to stand out historically. Gamification is understood as a promising, almost “salvific” resource in facing the challenges imposed by distance education. Pedagogical practice is analyzed based on the incorporation of playful elements, such as digital games, which stimulate critical thinking, favor cognitive development, and reposition the student as the protagonist of their learning process, that is, as the author of knowledge. In addition to gamification, the article addresses the use of active methodologies, such as project-based learning, hybrid teaching, and the flipped classroom, which break with traditional teaching models and seek greater student engagement. E-learning is also discussed, a form of teaching mediated by digital technologies and social networks, which expands the possibilities of access to knowledge, but also reveals contradictions, such as the false sense of balance promoted by digital platforms, while accentuating social inequalities. The article is based on a literature review and an interview published with Professor Nelson Pretto, renowned for his defense of critical, militant, and transformative education. We analyze the author’s emphasis on the role of digitization in the educational process, focusing on the importance of democratizing communication, the use of free software in the school environment, and the discussion about internet ownership, which is often concentrated in the hands of large corporations. The article proposes a profound reflection on the paths of education in the digital age, considering both the potential and the risks of technologies, especially with regard to autonomy, inclusion, and social justice in the educational environment.